Estudio de la normativa de establecimiento de salud amigo de la madre y el niño (ESAMYN) Hospital General Martin Icaza. Noviembre 2023 - abril 2024. - Troya Delgado, Madelen Katherine (2024)
The present research work focused on the study of compliance with the ESAMyN regulations at the Martín Icaza General Hospital, emphasizing the prenatal components and breastfeeding, a very important topic that today the health system is prioritizing, the objective of the research was to analyze compliance with the prenatal component as an indicator of the ESAMYN Regulations at the Martin Icaza General Hospital. The methodology used in the research was the quantitative approach, basic, field, descriptive, prospective and transversal. A systematic and non-participant observation was carried out to collect data on compliance with the prenatal component of the Regulations. A finite sample was used that included all health personnel and all pregnant women who received prenatal care at the hospital during the study period. The research techniques and instruments included a structured observation guide to evaluate prenatal care and the review of pregnant women's medical records. It is concluded that compliance with the prenatal component of the ESAMYN Regulations at the Martín Icaza General Hospital varies according to different aspects evaluated, with areas of satisfactory compliance, but also areas of deficiency. The importance of implementing corrective actions to improve compliance is highlighted, including continuous training for health personnel, promotion of community participation and regular supervision by health authorities.